Prospects of Application of Ultramicroelectrode Ensembles for Voltammetric Determination of Compounds with Close Standard Electrode Potentials and Different Diffusion Coefficients - Andrey Yu. Arbenin; Alexey A. Petrov; Denis V. Nazarov; Evgeny Serebryakov; Sergey O. Kirichenko; Petr S. Vlasov; Elena G. Zemtsova; Vladimir M. Smirnov; Elena E. Danilova; Sergey S. Ermakov; Alexander Vorobyov; Mikhail S. Mukhin; et al. (Chemosensors, 2022)
The spherical diffusion that occurs when using ultramicroelectrodes (i.e., electrodes with a characteristic size of 1–10 µm) contributes to a higher mass transfer rate. This leads to equalization of the depletion rates of the near-electrode layer due to the electrochemical reaction and to the supply of the product from the solution depth. This is the reason why, for ultramicroelectrodes, a limiting size of the spherical layer exists in which the concentration gradient is localized (diffusion layer). Thus, a stationary mass transfer mode is achieved, which is expressed in the sigmoidal CV curve’s shape. In ultramicroelectrode arrays, when the diffusion hemispheres are separated, a steady-state diffusion is realized. However, with a decrease in the interelectrode distance, which leads to the diffusion spheres intersection, a mixed regime arises, which is not fully time-independent. The resulting voltammogram’s shape change can serve as an analytical signal in the study of substances with differing diffusion coefficients, since the diffusion layer growth rate and, consequently, the area of intersection of neighboring spheres, depends on it. This work shows the applicability of voltammetry using ensembles of ultramicroelectrodes operating in the transient mode for the analysis of mixtures of electrochemically active compounds with close electrode reaction parameters, such as exchange currents and electrode potential. Ferrocenemethanol esters are used as an example. The applicability of cyclic voltammetry on the UME array for analysis of mixtures was illustrated by means of finite element modelling. The reliability of the modelling results was experimentally proved for ferrocenemethanol esters with glycine and triglycine.